India's GVC integration: An analysis of upgrading efforts and facilitation of lead firms - Saon Ray; Smita Miglani (Indian Council for Research on International Economic Relations (ICRIER), 2020)
India presents an unique example of manufacturing capability in most sectors, but low integration into GVCs. This paper examines the reasons for India's low integration into GVCs, especially in the manufacturing sector. It argues that one of the reasons for India's low integration into GVCs is its primary focus on the domestic market. The second reason for India's limited role is the role played by the lead firms. In this paper, we show that while India has several horizontal and vertical policies, there are fewer instances of GVC specific policies which lead to the encouragement of lead firms. The policy implications from the paper are the processes that emerging countries can follow in nurturing lead firms
Keywords: F16; F23; L23; L25; L60; O25; 330; Global value chains; industrial policy; integration; upgrading; lead firms